Effect of COVID-19 Infodemic on Media Trust and Perceived Stress - Shamsudeen Ademola Sanni; Neema Rajabu; Chinecherem Umezuruike; Lasisi Kamoru Alamu (Masters Program in Public Health, Sebelas Maret University, 2021)
Background: Health infodemic undermines public health response, results in poor observance of public health measures and costs lives. Health campaigns will not produce intended results without controlling misinformation. This study aimed to analyzed the correlation between infodemic, COVID-19 stress and media trust.Subjects and Method: This was a cross sectional study conducted using online structured questionnaire, from December 2020 to January 2021. A total of 470 participants among African twitter community were randomly selected for this study. The dependent variables were COVID-19 stress and media trust. The independent variable was while Infodemic serve. The data was analysed using Pearson’s product moment correlation coefficient test.Results: COVID-19 stress (r= 0.369; p<0.001) and media trust (r= 0.301; p<0.001) were correlated with infodemic and it was statistically significant.Conclusion: infodemic is correlated with COVID-19 stress and media trust.Keywords: infodemic, health communication, media trust, stress, COVID-19Correspondence: Sanni Shamsudeen Ademola. Department of Computer Science, Faculty of Science and Engineering, University of Eswatini, Private Bag 4, Matsapha, manzana, Kingdom of Eswatini. Email: sanniade01@gmail.com. Mobile: +26876241155/79241155.Journal of Health Promotion and Behavior (2021), 06(02): 144-153DOI: https://doi.org/10.26911/thejhpb.2021.06.02.07